Microbial responses to inorganic nutrient amendment overridden by warming: Consequences on soil carbon stability. (30th August 2018) - Wang, Mengmeng; Ding, Junjun; Sun, Bo; Zhang, Junyu; Wyckoff, Kristen N.; Yue, Haowei; Zhao, Mengxin; Liang, Yuting; Wang, Xiaoyue; Wen, Chongqing; Zhou, Jizhong; Yang, Yunfeng
Summary: Eutrophication and climate warming, induced by anthropogenic activities, are simultaneously occurring worldwide and jointly affecting soil carbon stability. Therefore, it is of great interest to examine whether and how they interactively affect soil microbial community, a major soil carbon driver. Here, we showed that climate warming, simulated by southward transferring Mollisol soil in agricultural ecosystems from the cold temperate climate zone (N) to warm temperate climate (C) and subtropical climate zone (S), decreased soil organic matter (SOM) by 6%–12%. In contrast, amendment with nitrogen, phosphorus and potassium enhanced plant biomass by 97% and SOM by 6% at the N site, thus stimulating copiotrophic taxa but reducing oligotrophic taxa in relative abundance. However, microbial responses to nutrient amendment were overridden by soil transfer in that nutrient amendment had little effect at the C site but increased recalcitrant carbon‐degrading fungal Agaricomycetes and Microbotryomycetes taxa derived from Basidiomycota by 4‐17 folds and recalcitrant carbon‐degrading genes by 23%–40% at the S site, implying a possible priming effect. Consequently, SOM at the S site was not increased by nutrient amendment despite increased plant biomass by 108%. Collectively, we demonstrate that soil transfer to warmer regions overrides microbial responses to nutrient amendment and weakens soil carbon sequestration.